PERJANJIAN JUAL BELI BARANG SECARA INTERNASIONAL MENURUT UPICCs DAN CISG SERTA KUHPERDATA - ROTUA DESWITA RAJA GUK GUK (PREMISE LAW JURNAL, 2013)
In International trade, transaction could not be separated from a contract. It is not simple to connect the agents in the International business. This case was concerned with the difference national law system, paradigm, and the established regulation as rule enforcement to be obeyed by the agents of each country. With existence unification and harmony regulation and practice through some efforts, through the UPICCS and CISG for Indonesia in The Indonesia Civil Codes (KUHPerdata) which was expected to reduce the difference of an obstacle for Indonesia as well as to the same point of view which eased the agents to fulfill law needs in International transaction agreement. The managing of right and duty between seller and buyer in International transaction agreement, conducting international transaction agreement to the agents and system of compensation fee effect to the unfulfilled agreement of the transaction based on UPICCs, CISG convention and KUHPerdata. Kata Kunci: Agreement, International Trading, UPICCs, CISG, KUHPerdata